2011
DOI: 10.4314/ajtcam.v8i3.65285
|View full text |Cite
|
Sign up to set email alerts
|

Neuropharmacological effects of Nigerian honey in mice

Abstract: Honey is a natural sweet substance that bees produce by transforming flower nectar or other sweet secretions of plants. It has widespread use in traditional medicine in various parts of the world. It has been reported to assist in building the entire central nervous system. The beneficial effects of honey have been attributed to the possible polyphenolic contents and some other constituents. The geographical locations and the sources of plant nectars may contribute to the effects of honey samples. Thus, we eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 43 publications
(36 reference statements)
2
36
0
Order By: Relevance
“…31 Also, some studies showed that the NHO could induce inhibitory effects on locomotion only at high doses. 32 Morphine is known as one of the significant opioids, and the possibility of its addiction is high. Previous studies on opioids, especially morphine have shown that long-term use of morphine stimulated glia cells in the spinal and supra-spinal cord, 33 and immune system and increased production of pro-inflammatory cytokines such as IL-1β, 6 and TNF-α , as well as the occurrence of neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…31 Also, some studies showed that the NHO could induce inhibitory effects on locomotion only at high doses. 32 Morphine is known as one of the significant opioids, and the possibility of its addiction is high. Previous studies on opioids, especially morphine have shown that long-term use of morphine stimulated glia cells in the spinal and supra-spinal cord, 33 and immune system and increased production of pro-inflammatory cytokines such as IL-1β, 6 and TNF-α , as well as the occurrence of neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Nectar conceivably has beneficial shrewdness of morphine-induced oxidative stress, to be able to enhance the reliance and tolerance in opiate dependency, human beings, some other contemplate designated that lessening in oxidative stress in opiate addicts will lower dependence and withdrawal indications 7 . We as a great deal as this time precise that nectar fortifies a vital antinociceptive impact 16 and has a positive impact on morphine analgesia and can be a sturdy association with pain control 17 . Withdrawals from opiates can cause digestive problems which include nausea and diarrhea similarly to muscle pain and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…In many investigations, the therapeutic effect of honey has been proven to improve or prevent diseases' progression (in humans and animals), in which some of them are recorded as follows: antifungal, antibacterial, and antiviral (Anthimidou & Mossialos, ; Candiracci et al, ; León‐Ruiz et al, ), antioxidant (Alves, Ramos, Gonçalves, Bernardo, & Mendes, ; Nayik & Nanda, ), radioprotective (Ahmad et al, ), prebiotic, and probiotic (Ammar, Ismail, Khalil, & Eid, ; Bakr, Mohamed, Tammam, & El‐Gazzar, ), antidepressant and anxiolytic (Akanmu et al, ; Al‐Rahbi, Zakaria, Othman, Hassan, & Ahmad, ), anti‐osteoporosis (Mohd Effendy, Mohamed, Muhammad, Mohamad, & Shuid, ), cardioprotective (Khalil, Tanvir, Afroz, Sulaiman, & Gan, ), and antitumor (Ahmed & Othman, ; Erejuwa, Sulaiman, & Wahab, ).…”
Section: Introductionmentioning
confidence: 99%